2020
DOI: 10.1128/iai.00500-20
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila and Its Pili-Like Protein Amuc_1100 Modulate Macrophage Polarization in Experimental Periodontitis

Abstract: Periodontitis is a chronic inflammatory disease triggered by dysbiosis of the oral microbiome. Porphyromonas gingivalis is strongly implicated in periodontal inflammation, gingival tissue destruction and alveolar bone loss through sustained exacerbation of the host response. Recently, the use of other bacterial species, such as Akkermansia muciniphila, has been suggested to counteract P. gingivalis elicited inflammation. In this study, the effect of A. muciniphila and its pili-like protein Amuc_1100 was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 71 publications
1
30
0
1
Order By: Relevance
“…In vitro, we observed that IL-10 was increased only when bone marrow macrophages were exposed to A. muciniphila. These results were corroborated in a more recent study (Mulhall et al, 2021), where in vivo administration of A. muciniphila and the pili-like protein Amuc_1100 resulted in an increased population of M2 macrophages as well as increased gene and protein expression of IL-10 within the gingival tissue (Mulhall et al, 2021). As noted by Janket et al, IL-10 produced by macrophages can contribute to the restoration of the epithelial barrier observed in vivo.…”
supporting
confidence: 55%
“…In vitro, we observed that IL-10 was increased only when bone marrow macrophages were exposed to A. muciniphila. These results were corroborated in a more recent study (Mulhall et al, 2021), where in vivo administration of A. muciniphila and the pili-like protein Amuc_1100 resulted in an increased population of M2 macrophages as well as increased gene and protein expression of IL-10 within the gingival tissue (Mulhall et al, 2021). As noted by Janket et al, IL-10 produced by macrophages can contribute to the restoration of the epithelial barrier observed in vivo.…”
supporting
confidence: 55%
“…Previously, we had demonstrated that oral administration of viable A. muciniphila or pili‐like protein Amuc_1100 during experimental periodontitis resulted in decreased alveolar bone loss, increased IL‐10 production, and decreased pro‐inflammatory IL‐12 secretion, contributing to the prevention of periodontal destruction (Huck et al, 2020; Mulhall, DiChiara, et al, 2020). In this study, beyond validating our previous results, we also observed that pasteurized A. muciniphila led to comparable local and systemic anti‐inflammatory effects in both lean and obese animals.…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia muciniphilia , a novel probiotic, has been shown to counteract P. gingivalis‐ induced tissue damage, especially alveolar bone loss, in models of experimental periodontitis (Huck et al, 2020; Mulhall, DiChiara, et al, 2020). This muciniphilic gram‐negative bacterium is found throughout the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…The gene coding for Amuc_1100 can be transferred into Escherichia coli, which then acquires Akk-like features with respect to the suppression of obesity [30]. Moreover, recombinant Amuc_1100 has antiobesity [18] as well as anti-inflammatory effects in mice, for example in mouse models of colitis [31] and experimental periodontitis [32]. A clinical study that compared the effects of pasteurized versus live Akk led to the conclusion that the pasteurized bacterium was more efficient than the live one [19].…”
Section: Aging Discussionmentioning
confidence: 99%